(untitled) (Academia Journal of Medicine, 2020)
Background: Diabetes is a metabolic disorder that can affect nearly every organ system in the body. Recently, Vitamin D3 was given some importance worldwide in the pathogenesis of diabetes. The extraskeletal effects of Vitamin D3 have attracted considerable interest. The identification of 1,25-Dihydroxyvitamin D3 and 1-Alpha-Hydroylase expression in pancreatic Beta cells, in cells of the immune system,and in various other tissues besides the bone system , supports the role of Vitamin D3 in the pathogenesis of type 2 diabetes. Vitamin D3 deficiency appears to be related to development of diabetes mellitus type 2 and metabolic syndrome. The aim of the study is to find out whether this correlation between vitamin D and Diabetes is present or not. Mainly in this study we have tried to correlate Vitamin D with HbA1C levels in patients with Type 2 diabetes mellitus. Subjects and Methods: The present one and half years, cross sectional study was carried out in department of medicine, Darbhanga Medical College and Hospital, Darbhanga, Bihar from March – 2018 to September – 2019. A total of 125 patients with type 2 Diabetes Mellitus were studied. The estimation of vitamin D was done. Using Siemens, ADVIA centraurVit D assay a one pass 18 minute antibody competitive immunassay. Results: Maximum no. of cases was in the age group of 51 to 60 that is 40 patients (32%). The mean age of studied population was 60.22 +- 11.65 years. Out of 125 patients 77(61.6%) were males and 48 patients (38.4%) were females, with a ratio of male to female of 1.60:1. In 104 patients (83.2%), the level of vitamin D were below normal, in 11 patients (8.8%) the levels insufficient and in remaining 10 patients , the levels were either normal or more than normal. Conclusion: There was an inverse association between Vitamin D and HbA1C in patients with type -2 Diabetes Mellitus. Lower Vitamin D levels are associated with poor glycemic control. That means in case of low Vitamin D the study reveals high HbA1C. Vitamin D deficiency is prevalent in Diabetes mellitus Type 2 so by supplementation of vitamin D we can improve glycemic controls in patients of Diabetes mellitus Type 2. By improving glycemic control, we can reduce the complication of Diabetes.